Unveiling drivers and barriers in advancing agricultural wastewater reuse in Southern Italy: A SWOT analysis informed by stakeholder insights - Kledja Canaj; Andi Mehmeti (Cleaner Water)
In the Apulia region (Southern Italy), the issue of water scarcity is escalating, making wastewater reclamation and reuse crucial options for promoting sustainable development. Despite substantial financial investments, the practical adoption of wastewater reuse for agricultural irrigation remains constrained. Using a quantitative SWOT framework, we analyzed market, social, and product-related factors impacting water reuse. A questionnaire with 23 out of 30 expert stakeholders, including researchers, public administration officials, utility members, farmers, and engineers, was used to evaluate the significance of each aspect identified in the SWOT analysis. The key drivers of a wastewater-reuse-based economy include improved water availability during drought, a commitment to the circular economy, and existing successful agricultural reuse projects. Conversely, identified obstacles encompass the lack of storage basins for storing wastewater between seasons to synchronize production with crop water needs, inadequate political dedication to oversee groundwater withdrawals, difficulties in controlling investments, and bureaucratic demands arising from stringent regulation. Underpinned by the recently enacted EU Water Reuse Regulation, the reuse of wastewater is crucial for addressing water scarcity, mitigating aquifer over-exploitation, and achieving objectives related to the circular economy. However, moving forward, an updated governance framework integrating continuous monitoring, active stakeholder engagement, and investments in intermediate storage facilities is imperative for effective and sustainable wastewater reuse. This research provides novel empirical evidence and expands upon existing studies on barriers and opportunities related to reclaimed water in a Mediterranean context and regions facing similar challenges. The findings can serve as a valuable reference for future research in this field.